SMART LKS: MODEL APLIKASI PEMBELAJARAN BERBASIS TEKNOLOGI MOBILE UNTUK PENGAYAAN BAHAN AJAR SEKOLAH DASAR PASCA PEMBELAJARAN DI KELAS - bahar (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Abstract There are many obstacles faced by teachers in making maximum use of time to deliver lessons in class so that learning time becomes ineffective, resulting in not conveying all teaching materials. Thus the learning objectives are not maximally achieved. Various attempts have been made to enrich the learning material to improve students understanding of post-learning elementary school in the classroom outside of formal learning time, such as the use of various types of learning media to study independently. The use of Information Technology such as e-learning, e-module, Interactive Learning CD has been used to help students in the learning process independently, but these media have their advantages and disadvantages. This paper offers a Mobile Technology model as a medium that can be used by teachers to assist in enriching Teaching Materials to improve understanding of Post-Learning Elementary School students in the classroom. This proposed model is expected to cover the weaknesses of each existing media : e-module, elearning, and Interactive Learning CD, because it provides a very interactive, practical facility whenever and wherever students can use it, as well as presenting interesting learning materials and practice questions, so as to motivate students in learning.